2018
DOI: 10.17221/92/2018-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cardiorespiratory effects of the alpha-2 adrenoceptor agonists xylazine, medetomidine and dexmedetomidine in combination with ketamine in dogs

Abstract: In this study, we compared the effects of xylazine, medetomidine and dexmedetomidine in combination with ketamine on heart rate, respiratory rate, blood gas values, temperature and sedation scores. A total of 30 dogs were evaluated. The dogs were randomly allocated into three anaesthesia groups, each of which included ten dogs. The first group, denoted the xylazine/ketamine group, intravenously received xylazine (0.5 mg/kg) for premedication and ketamine (5 mg/kg) for induction. The second group, the medetomid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Among the 222 trials initially identified from the search strategy, 13 studies were included in this meta-analysis [ 17 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], involving a total of 576 dogs of various breeds. Most of the selected dogs were classified as having ASA 1 and ASA 2 physical status.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the 222 trials initially identified from the search strategy, 13 studies were included in this meta-analysis [ 17 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], involving a total of 576 dogs of various breeds. Most of the selected dogs were classified as having ASA 1 and ASA 2 physical status.…”
Section: Resultsmentioning
confidence: 99%
“…The authors investigated doses of dexmedetomidine ranging from 1 to 10 μg.kg −1 (1 μg.kg −1 ≈25 μg.m −2 ) [ 17 , 27 , 29 , 31 , 35 ], combined with methadone [ 24 , 28 ], ketamine [ 32 , 37 ] or buprenorphine [ 26 , 32 , 35 , 36 ] as premedication. Four included trials used alfaxalone to induce or maintain anesthesia [ 26 , 29 , 33 , 35 ], and eight used propofol [ 17 , 28 , 30 , 31 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations